Empowering the Future Workforce: Transitioning Higher Education To wards Society 5.0 (Trinity Journal of Management, IT & Media (TJMITM), 2025)
Society 5.0, and Education 5.0, provide innovative solutions to modern societal challenges by integrating technology with human-centric approaches, envisioning a future in which AI, IoT, and big data enhance well-being. Education 5.0 adapts to the evolving job market driven by Industry 4.0, focusing on personalized learning. This article investigates the relationship between Society 5.0, and Education 5.0, emphasizing the importance of collaboration between educational institutions and industries to develop a workforce capable of navigating a technology-driven world, fostering innovation, inclusivity, and sustainability. The impact of globalization and technological advancement on education within Society 5.0 is significant. This study examines how Higher Education 5.0 (HE5.0) prepares the future workforce by emphasizing digital literacy, interdisciplinary learning, ethical reasoning, and industry collaboration. Utilizing a mixed-methods approach, this research explores the intersection of gender and socioeconomic background in acquiring digital skills, compares global HE5.0 implementation, and provides policy recommendations. The findings reveal disparities based on gender and socioeconomic status, but also that HE5.0, enhances digital skills and soft competencies. Recommendations are offered to universities, policymakers, and industries to create inclusive industry-aligned curricula. Future research should include long-term studies of HE5.0 effects and policy-driven digital inclusion.
Keywords: Higher Education 5.0 (HE5.0); Society 5.0; digital literacy; interdisciplinary learn ing; ethical reasoning; industry collaboration; future workforce; digital skills acquisition; gender intersectionality; socioeconomic background; global education comparison; inclusive curricu la; industry-aligned education; digital inclusion; education policy